Osteossíntese de fratura salter-harris tipo IV em cotovelo de buldogue francês – relato de caso - Sfalcin, Juliana Corrêa (Universidade Federal do Tocantins, 2022)
The Supervised Curricular Internship was performed in two different places and divided in two periods. The first period was performed at the Clínica Veterinária Dog & Cia in the areas of Small Animal Medical and Surgical Clinic, from May 11th to June 25th, 2021, under the supervision of the Veterinary Doctor Rodolfo Olinto Rotoli Garcia de Oliveira. The second period of the internship occurred at the University Veterinary Clinic of the Universidade Federal do Tocantins (CVU/UFT), in the area of Small Animal Surgical Clinic, from June 26th to July 9, 2021, under the supervision of Dr. Flávia Augusta de Oliveira. Altogether, the internship accounted for 400 hours. During these periods, the hospital routine was monitored in both places, being possible to monitor and participate in clinical, surgical, emergency and nursing care for patients. This report describes the conditions of the internship in these places, the accompanied casuistry, the procedures performed and presents a report of an orthopedic case of osteosynthesis of a Salter Harris type IV fracture in a French Bulldog's elbow.